Biosynthesis of L-Tryptophan by E. coli grown on coconut water medium - Allan Anthony G. Ortiz. 4 0 16; 5 (2003)
u
Thesis: (Bachelor of Science in Chemistry) - Pamantasan ng Lungsod ng Maynila, 2003.
Keywords: 2 -- 0; 6; 20; 20; 2